Acute management of dengue shock syndrome: a randomized double-blind comparison of 4 intravenous fluid regimens in the first hour. - Ngo, N; Cao, X; Kneen, R; Wills, B; Nguyen, V; Nguyen, T; Chu, V; Nguyen, T; Simpson, J; Solomon, T; White, N; Farrar, J (2001)
Dengue hemorrhagic fever is an important cause of morbidity among Asian children, and the more severe dengue shock syndrome (DSS) causes a significant number of childhood deaths. DSS is characterized by a massive increase in systemic capillary permeability with consequent hypovolemia. Fluid resuscitation is critical, but as yet there have been no large trials to determine the optimal fluid regimen. We undertook a randomized blinded comparison of 4 fluids (dextran, gelatin, lactated Ringer's, and "normal" saline) for initial resuscitation of 230 Vietnamese children with DSS. All the children survived, and there was no clear advantage to using any of the 4 fluids, but the longest recovery times occurred in the lactated Ringer's group. The most significant factor determining clinical response was the pulse pressure at presentation. A comparison of the colloid and crystalloid groups suggested benefits in children presenting with lower pulse pressures who received one of the colloids. Further large-scale studies, stratified for admission pulse pressure, are indicated.